What are dictations useful for? Representations of future primary teachers - Cicres, Jordi; Llach, Sílvia (Didáctica. Lengua y Literatura, 2019)
The aim of this paper is to analyse pre-service primary teachers’ knowledge and beliefs about dictation, an activity that has been interpreted in different ways according to distinct theories of teaching and learning. In order to do this, we have designed a questionnaire composed of open-ended questions and have administered it to 150 students from the second course of the Primary-School Education degree and the double degree in Primary-School Education and Early Childhood Education at the University of Girona (before their practicum periods). The results of the questionnaire have been analysed using qualitative techniques and hierarchical clustering. Data revealed that most students only know between two and three different dictation methods, although some students mention up to five. Considering its uses, we have observed that the interviewed students understand that the predominant use of this activity is to improve or assess knowledge of spelling. These two aspects, the predominant types and uses, were also grouped in the statistical analysis. In relation to this, the paper presents final recommendations to foster more diverse dictation practices, and to integrate them in a natural way into the cohesive pedagogical practices of each school, in line with contemporary views of learning.
Keywords: dictations; listening; representations; spelling